Real time weather surveillance via lab view interfaced arduino - Anil Mungekar, Abhishek; Kalpesh Solanki, Yashraj; Swarnalatha, R. (International Journal of Engineering and Technology, 2018)
Background: In modern day scenario, especially in the United Arab Emirates, many fluctuations can be seen in the climatic conditions. These type of climate changes can adversely affect the workplace environment of several industries, their transport lines, and as well as day to day functioning of various other human activities.Approach: The idea proposed, is an all-inclusive metrological real time weather monitoring system using the advanced Bosch barometric pressure sensor BMP180 and Adafruit humidity sensor DHT22. The monitoring is achieved by making use of efficient virtual simulation (LabVIEW) which is directly interfaced with ATmega328 quartz crystal 16 MHZ microprocessor.Results: From the real time LabVIEW display, several weather parameters are monitored, in an attempt to maintain them below a certain required threshold. Conclusions: The results suggest a setup that makes the entire monitoring process cost effective and easy to operate due to its user friendly interface.Â Â